Comparative analysis of changes in body composition of young volleyball players during the season - Sieroń, Adrian; Kołodyńska, Gabriela; Rostojek, Paulina (Journal of Education, Health and Sport, 2018)
Introduction. The possibility of achieving the highest successes in sport competition is associated with the constant selection from the youngest years of volleyball. Volleyball skills and somatic predispositions are an important factor influencing the selection of juvenile athletes to the representation of the region and national representations. Material and methods. Diagnosis and monitoring of the development of talented athletes enables the selection of the most talented individuals and information for trainers to individualize the development of their proteges. The aim of this work is to compare the changing somatic features during the season in teenage volleyball players. 47 men aged 14-15, who played on the same level of competition, were qualified for the study. The tests were carried out twice before the start league and at the end of the season. The measurement data of 16 somatic features were used. Results and summary. The presented results prove significant changes in individual somatic features during the season. Impact of personal development and training loads, there have been significant changes in the development of the skeleton and muscularity of volleyball players.